Tailoring of cholesteric plane spacing, dielectric relaxation and optical properties of high temperature chiral nematic phase by UV irradiation. (22nd January 2016) - Singh, Dharmendra Pratap; Vimal, Tripti; Kumar Gupta, Swadesh; Tripathi, Prachi; Varia, M. C.; Kumar, Sandeep; Manohar, Shashwati; Manohar, Rajiv
Abstract: The effect of Ultra Violet (UV) irradiation on the high temperature chiral nematic (N * ) mesophase has been investigated. The controlled UV exposure produced bending in rod shape molecules. The bending of molecules affects their long molecular axis; therefore, the relaxation mode associated with the rotation of molecules along the long molecular axis shifts toward the higher frequency. The UV irradiation also increases the cholesteric plane spacing of N * LC molecules. The a.c. conductivity of N * LC has been increased enormously after UV irradiation. The efficiency of opto-dielectric effect has also been evaluated with the variation of bias voltage in the present investigation.